Efficient exclusion - Espen R. Moen; Christian Riis (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2005)
In an important paper, Aghion and Bolton (1987) argue that a buyer and a seller may agree on high liquidation damages in order to extract rents from future suppliers. As this may distort future trade, it may be socially wasteful. We argue that Aghion and Bolton's' analysis is incomplete in some respects, as they do not model the entry of new suppliers. We construct a model where entry is costly, so that entering suppliers have to earn a quasi-rent in order to recoup the entry cost. Reducing an entrant's profits by the help of a breach penalty then reduces the probability of entry in the first place, thus making a breach penalty less attractive for the contracting parties. We show that the initial buyer and seller only have incentives to include a breach penalty if there is excessive entry without it. Forcing the initial buyer and seller to eliminate the breach penalty reduces welfare.
Keywords: L42; 330; Exclusive contracts; breach penalties; entry; efficiency